Multi‐organ dysfunction syndrome in patients undergoing extracorporeal life support. Issue 9 (1st May 2022) - Kozakov, Kostiantyn; Philipp, Alois; Lunz, Dirk; Lubnow, Matthias; Provaznik, Zdenek; Keyser, Andreas; Rupprecht, Leopold; Schmid, Christof; Schopka, Simon
Abstract: Background: Multiple organ failure is a common complication in patients undergoing ECLS significantly affecting patient outcomes. Gaining knowledge about the mechanisms of onset, clinical course, risk factors, and potential therapeutic targets is highly desirable. Methods: Data of 354 patients undergoing ECLS with one‐, two, three‐, and four organ failures were retrospectively analyzed. Incidence of multiple organ dysfunction (MODS), its impact on survival, risk factors for its occurrence, and the impact of proinflammatory mediators on the occurrence of MODS in patients undergoing ECLS were investigated. Results: The median follow‐up was 66 (IQR 6; 820) days. 245 (69.2%) patients could be weaned from ECLS, 30‐day survival and 1‐year survival were 194 (54.1%) and 157 (44.4%), respectively. The duration of mechanical support was 4 (IQR 2; 7) days in the median. Increasing severity of MODS resulted in significant prolongation of mechanical circulatory support and worsening of the outcome. Liver dysfunction had the strongest impact on patient mortality (OR = 2.5) and survival time (19 vs 367 days). The serum concentration of analyzed interleukins rose significantly with each, additional organ affected by dysfunction ( p < 0.001). All analyzed proinflammatory cytokines showed significant predictivity relative to the occurrence of MODS with interleukin 8 serum level prior to ECLS showing the strongest predictive potential for the occurrence of MODS (AUC 0.78). Conclusion: MODS represents a frequent complication in patients undergoing ECLS with a significant impact on survival. Proinflammatory cytokines show prognostic capacity regarding the occurrence and severity of multi‐organ dysfunction. Abstract : The inflammatory interleukins 6 and 8, as well as tumor necrosis factor α and soluble interleukin 2 receptor, indicate the risk for the occurrence and severity of multi organ dysfunction syndrome prior to initiation of mechanical circulatory support and early in the clinical course. Multi organ dysfunction syndrome is a common complication in the clinical course of extracorporeal life support with a strong impact on patient outcome, which worsens with each additional organ affected. The inflammatory interleukins 6 and 8, as well as tumor necrosis factor α and soluble interleukin 2 receptor, indicate the risk for the occurrence and severity of multi organ dysfunction syndrome prior to initiation of mechanical circulatory support and early in the clinical course.